(untitled) (PerCursos, 2021)
This article investigates the performance Notícias da América, by the artist Paulo Nazareth. It identifies discussions (and actions) that handle a plurality of pasts (ancestral, colonial) and, at the same time, open relational perspectives a-typical feature of contemporary art since the 1960s. In that performance, as Nazareth moves through Latin American cities, the images and discourses produced forge a common space between himself, his interlocutors and the landscape. Simultaneously, a multiple temporality emerges in which peripheral subjectivities become visible. It is also from this space-time relationship that other of his artistic productions (such as the series Aqui é arte) can be unfolded.